CRISPR Gene-Therapy: A Critical Review of Ethical Concerns and a Proposal for Public Decision-Making - Lange, Victor; Kappel, Klemens (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
CRISPR is currently viewed as the central tool for future gene therapy. Yet, many prominent scientists and bioethicists have expressed ethical concerns around CRISPR gene therapy. This paper provides a critical review of concerns about CRISPR gene therapy as expressed in the mainstream academic literature, paired with replies also generally found in that literature. The expressed concerns can be categorised into three types depending on whether they stress risk/benefit ratio, autonomy and informed consent, or concerns related to various aspects of justice. In the reviewed literature, we found no intrinsic objections to CRISPR gene therapy, even though many such objections were present in discussions of gene editing in the 1990s. The paper then proposes a brief outline for a practically applicable moral framework for public decision-making about CRISPR gene therapy and suggests how such a framework might be supported. We also suggest that this framework should govern public engagement about CRISPR gene therapy in order to reduce the risk that we make decisions about CRISPR gene therapy based on misperceptions, inflated views of risk, or unreasonable moral or religious views.